Bedazzled saints: catacomb relics in early modern Bavaria - Litaker, Noria ca. 20./21. Jh. (Studies in early modern German history, 2023)
"This book argues that whole-body saints (intact skeletons) in Bavaria functioned differently than the small, fragmented relics common in the medieval period. By devising and using this innovative relic presentation, early modern Bavarians materially expressed their loyalty to the universal Roman Catholic church and created local and exclusive patrons for their towns and villages"